Early-life allergen exposure and atopy, asthma, and wheeze up to 6 years of age. - Torrent,M; Sunyer,J; Garcia,R; Harris,J; Iturriaga,MV; Puig,C; Vall,O; Anto,JM; Newman,Taylor AJ; Cullinan,P (Am J Respir Crit Care Med, 2007)
RATIONALE: Although it is widely assumed that the incidence of childhood respiratory allergies to common aeroallergens is directly related to allergen exposure in early life, few longitudinal studies have investigated this issue, and available data are scarce and mainly limited to high-risk groups. OBJECTIVES: To assess, in a prospective manner and in a general population, the role of early life exposures to Der p1 and Fel d1 on the inception of sensitization and asthma. METHODS: Pregnant women and their children were recruited for the Asthma Multicentre Infant Cohort Study. Overall, 1,611 newborns were initially enrolled in three cohorts in the United Kingdom and Spain. Der p1 and Fel d1 allergens were measured in household dust samples at 3 months of age for 1,474 (91.5%) participants, and skin prick tests were performed at 6 years of age on 1,182 (80.2%) participants. Wheeze and diagnosed asthma were reported in yearly questionnaires. MEASUREMENTS AND MAIN RESULTS: Exposure to Der p1 early in life was not related to a positive specific prick test or to asthma or persistent wheeze at 6 years of age. Fel d1 showed an association with all these outcomes (third vs. first tertile; odds ratio, 4.43 for positive specific prick test and 2.6 for diagnosed asthma). CONCLUSIONS: Dose-response relationships between allergen exposure and sensitization or asthma may be allergen specific and nonlinear; a minimum threshold level is needed to induce sensitization, but no dose-response relationship exists above this level. The effect of a particular allergen seems to be similar on atopy and asthma inception.